Sintesis dan Karakteristik CaCO3 dari Cangkang Kerang Kepah (Polymesoda erosa) sebagai Doping Anoda Baterai Lithium-Ion - Trisakti, Yunior; Miratsi, Lizia; Kurniawan, Widodo Budi (Jurusan Fisika, Universitas Bangka Belitung, 2022)
Synthesis and Characteristics of CaCO3 from Kepah Clam Shells (Polymesoda erosa) as Anode Doping of Lithium-Ion Batteries LTO (Lithium Titanate Oxide) or Li4Ti5O12 is one of the candidates for graphite replacement anode material in the production of Lithium-ion batteries. However, LTO materials have the disadvantage of low electrical conductivity, which limits the working level of the battery. Kepah clam shells are one of the wastes that have not been widely used even though the amount is still very abundant, and is expected to have the potential to be in the source of CaCO3 because it contains high amounts of calcium. Therefore, this study aims to determine the content of CaCO3 in the shell of the kepah clam (Polymesoda erosa) and determine the conductivity value of the LTO anode doped with CaCO3 of the kepah clam shell. The synthesis method used is the solid state reaction method with variations in doping concentrations of 0.00 mol, 0.10 mol, 0.15 mol, and 0.20 mol. The results of XRF analysis on the shell powder showed that the most dominant element content was Ca which was 97.63%. So it shows that calcium carbonate (CaCO3) from the shells of kepah mussels was successfully prepared. Furthermore, the anode active material was obtained, which if obtained XRD results and analyzed would show the absence of the CaCO3 phase, and there was no doping influence, then the active material powder was synthesized Li4Ti5O12 anode sheet doped CaCO3 shell. As for knowing the conductivity value of the Li4Ti5O12 anode sheet doped by CaCO3 clam shells, it is further characterized using Electrochemical Impedance Spectroscopy (EIS).